Rotacism in the articulation of children in Santo Amaro – Bahia - Muniz, Eliana (2024)
In this paper, we analyze the rotacism in the speech of children in the literacy process of Santo Amaro – BA, checking if the occurrences are regular in terms of linguistic and social aspects. The research considers that rotacism occurs due to the similarity of features between the consonants /l/, /ɾ/ and /r/ (CHOMSKY; HALLE, 1968). For the research, recordings were made with 3 girls and 3 boys, attending the 2nd year of elementary school. The tests were divided into four contexts: complex onset with /l/ and with /ɾ/, coda with /l/ and coda with /R/, with image naming tests and word reading tests, with a total of 36 words. The results showed the occurrences of the phenomenon, mainly in the context of complex onset in words like plástico [ˈpɾastʃikʊ] and bicicleta [bisiˈkɾɛtɐ], and especially in naming tests, which seems to indicate the influence of spelling on rotacism. We also emphasize a pattern of occurrences in the stressed syllable and in the context of coda there were no occurrences of rotacism.